The Term Structure of Interest Rates in a Heterogeneous Monetary Union - James Costain; Galo Nu\~no; Carlos Thomas (Center for Economic Studies and ifo Institute (CESifo), 2022)
We build a no-arbitrage model of the yield curves in a heterogeneous monetary union with sovereign default risk, which can account for the asymmetric shifts in euro area yields during the Covid-19 pandemic. We derive an affine term structure solution, and decompose yields into term premium and credit risk components. In an extension, we endogenize the peripheral default probability, showing that it decreases with central bank bond-holdings. Calibrating the model to Germany and Italy, we show that a "default risk extraction" channel is the main driver of Italian yields, and that flexibility makes asset purchases more effective.
Keywords: E50; G12; F45; 330; sovereign default; quantitative easing; yield curve; affine model; Covid-19 crisis; ECB; pandemic emergency purchase programme